2017
DOI: 10.1111/ijac.12773
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue of three advanced SiC/SiC ceramic matrix composites at 1200°C in air and in steam

Abstract: K E Y W O R D Sceramic-matrix composites, fatigue, fractography, high-temperature properties, mechanical properties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 50 publications
3
40
0
Order By: Relevance
“…SiC‐SiC CMCs must support mechanical loads at high temperatures in combustion environments and in other types of oxidizing environments that typically have steam as one of the components . Recent studies report severe degradation of high‐temperature mechanical performance of SiC‐SiC composites in steam . Hi‐Nicalon™‐S SiC fibers are used in many of these SiC‐SiC CMCs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SiC‐SiC CMCs must support mechanical loads at high temperatures in combustion environments and in other types of oxidizing environments that typically have steam as one of the components . Recent studies report severe degradation of high‐temperature mechanical performance of SiC‐SiC composites in steam . Hi‐Nicalon™‐S SiC fibers are used in many of these SiC‐SiC CMCs .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Recent studies report severe degradation of high-temperature mechanical performance of SiC-SiC composites in steam. [10][11][12][13][14][15][16][17] Hi-Nicalon™-S SiC fibers are used in many of these SiC-SiC CMCs. 5,6 Oxidation can severely degrade SiC fiber strength, [18][19][20][21] and is therefore a vital concern for SiC-SiC CMCs, particularly in combustion environments and in steam.…”
Section: Introductionmentioning
confidence: 99%
“…As the crack grows, more regions are exposed to oxidative environment, causing embrittlement. Presumably embrittled areas transfer the load to remaining intact areas, which are incapable of carrying the load leading to final failure [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…All tests were carried out at 1200°C using a uniaxial testing machine (MTS model 810) and a Flex Test 40 digital controller (MTS Corp.). A detailed description of the experimental arrangement is provided elsewhere 18‐20 . Standard dogbone‐shaped specimens used in this study were machined by diamond grinding.…”
Section: Materials and Experimental Arrangementsmentioning
confidence: 99%
“…Consequently, mechanical properties of the composite deteriorate and component life is reduced. In fact, recent studies reported severe deterioration of the mechanical performance of SiC/SiC composites at elevated temperature in steam 17‐21 …”
Section: Introductionmentioning
confidence: 99%